Conversational Styles and Misunderstanding in Cross-Sex Conversations in Hes Just Not That into You Movie - Aryani, Ayu Nyoman (LLT Journal: A Journal on Language and Language Teaching, 2016)
Conversation is a social interaction among societies. In this case, gender differences in daily communication lead to mens and womens different point of views in performing styles of the conversations. Misunderstanding is likely to occur in crosssex conversations when the idea or thought are understood differently by men and women. This study was intended to analyze the use of conversational styles by men and women and also investigate the misunderstanding phenomena that happened in cross-sex conversations. The researcher identified that the conversational styles used by Alex as a male character in the cross-sex conversations were qualifiers, controlling the topics, verbal fillers, intensifiers, swear words, compound requests, tag questions, questions, interruptions, overlapping, and talk domination. Meanwhile, Gigi, as a female character used qualifiers, controlling the topics, verbal fillers, intensifiers, swear words, tag questions, questions, interruptions, overlapping, talk domination, and silence. In answering the second question, the researcher discovered factors that affected the misunderstanding in the cross-sex conversations between Alex and Gigi were involvement versus independence and message versus metamessage.